Development and evaluation of a consumer information resource, including Patient Decision Aid, for lung cancer screening: a quasi-experimental study. Issue 2 (10th March 2019) - Manners, David; Pettigrew, Simone; Lake, Fiona R; Piccolo, Francesco; McWilliams, Annette M; Brims, Fraser J H
Abstract: Lung cancer screening of high-risk individuals with computed tomography is a promising intervention to reduce lung cancer mortality. Patient Decision Aids (PtDAs) may assist eligible individuals assess the risks and benefits associated with screening. Screening preference is high among lower-risk, screening-ineligible individuals and strategies are needed to reduce screening demand among this group. We developed and evaluated a resource comprising a recruitment pamphlet combined with either a PtDA for screening-eligible individuals or an education pamphlet for screening-ineligible individuals. Quasi-experimental pre-post pamphlet exposure design. Ever-smokers aged 55–80 years attending hospital outpatient clinics were invited. Among screening-eligible participants, the assessed outcome was change in score on the Decisional Conflict Scale (DCS). Among screening-ineligible participants, the assessed outcomes were change in screening preference. In the study 51% (55/107) of invited individuals participated, with mean ± standard deviation age 66.9 ± 6.4 years, 53% (29/55) male, and 65% (36/55) eligible for screening. Median (interquartile range) DCS among screening-eligible participants reduced from 28.9 (22.7–45.3) pre-PtDA to 25 (1.6–29.7) post-PtDA ( p < .001), but there was no significant change in the proportion that reached the accepted threshold for decisional certainty (DCS < 25, 10/36 [28%] pre-exposure vs. 14/36 [39%] post-exposure, p = .1). Screening preference among screening-ineligible individuals reduced after viewing the screening-ineligible brochure (pre-exposure median of "Prefer" to post-exposure median of "Unsure, " p = .001). Our consumer information pamphlets about lung cancer screening may reduce decisional conflict and improve alignment of screening preference with eligibility.